2012 34th International Conference on Software Engineering (ICSE) 2012
DOI: 10.1109/icse.2012.6227105
|View full text |Cite
|
Sign up to set email alerts
|

Industrial application of concolic testing approach: A case study on libexif by using CREST-BV and KLEE

Abstract: As smartphones become popular, manufacturers such as Samsung Electronics are developing smartphones with rich functionality such as a camera and photo editing quickly, which accelerates the adoption of open source applications in the smartphone platforms. However, developers often do not know the detail of open source applications, because they did not develop the applications themselves. Thus, it is a challenging problem to test open source applications effectively in short time. This paper reports our experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Samsung Electronics and KAIST will continue collaboration to overcome such limitations (see Section VIII-C) [20], [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Samsung Electronics and KAIST will continue collaboration to overcome such limitations (see Section VIII-C) [20], [19].…”
Section: Discussionmentioning
confidence: 99%
“…This step requires human expertise on a target domain. For example, Kim et al [19] demonstrated that testing strategies on selecting symbolic input affects bug detection capability through a case study on the open source libexif library. 01:int main() { 02: int x, y,z, max_num=0; 03: CREST_int(x); // Declaration of x, y, z 04: CREST_int(y); // as symbolic integer 05: CREST_int(z); // variables 06: 07: if(x >= y) { 08:…”
Section: Generate a New Symbolic Path Formula ψ I Given A Symbolic mentioning
confidence: 98%
“…For example, when a PC contains complex constraints such as non-linear expressions or floating point operations of which SMT solvers cannot deal with efficiently [15,21], concolic testing can simplify the constraints with concrete values to solve it. Even though this concretisation may introduce imprecision, it allows concolic testing to generate input values where symbolic execution may not [17,10].…”
Section: Concolic Testingmentioning
confidence: 99%
“…Concolic analysis combines concrete and symbolic values in order to traverse all possible paths (up to a given length) of an application [6]. CCCD is innovative for several reasons.…”
Section: Introductionmentioning
confidence: 99%